Atribut Minuman Teh Kemasan Siap Minum yang Memengaruhi Persepsi Konsumen di Kabupaten Tegal - Dias Indrasti; Fina Siliyya (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
Ready-to-drink packaged tea drinks have various attributes affecting consumer perception. This study aims to identify the attributes of ready-to-drink packaged tea drinks that became the main concern, considered important, and affecting purchasing decisions by consumers in Tegal Regency. The method used was a purposive sampling survey. Data were analyzed by chi-square tests. The survey involved 150 respondents, which majority was woman (60.00%), aged 15-24 year (68.67%), had diploma/bachelor degree (54.67%), worked as student (50.67%), and earned less than Rp1,000,000 (62.67%) per month. As many as 93.34% respondent bought packaged tea drinks at minimarkets and grocery stalls for themselves (45.33%) and family (50.00%). Purchase made with a frequency of 1-2 times a week (35.33%) to once a month (40.66%). The attributes of packaged tea drinks were taste and aroma (38.67%), halal (29.33%), and expiration date (13.33%). The attributes of packaged tea drinks considered as very important were halal (92.67%), expiration date (82.00%), and taste and aroma (61.33%). Attributes of packaged tea drinks affecting purchasing decisions were taste and aroma (98.67%), expiration date (98.00%), and halal (96.67%). Taste and aroma was the main attributes that influence the perception of respondents in Tegal Regency in buying packaged tea beverage products.